An in-silico approach for the identification of natural compounds as potential BACE1 inhibitors for the treatment of Alzheimer disease - Tanishq Lodha, Sumit Birangal, Aravinda Pai, Santosh Prabhu, Sandhya Nayak, Tisa Francis, Lalit Kumar, Ruchi Verma (Journal of Applied Pharmaceutical Science, 2024)
BACE-1 is a transmembrane protein occurring in the endoplasmic reticulum that is responsible for generation of beta amyloid (Aβ) by cleavage of amyloid precursor protein (APP). Deposition and aggregation of Aβ in the brain results in the onset of Alzheimer’s disease (AD). The process of drug discovery in this area is sluggish and most of the developed molecules fail due to toxicity. Research related to phytochemicals has taken pace in drug discovery process due to associated low toxicity comparatively. The development of low toxicity BACE-1 inhibitors has proven to be a promising treatment strategy for AD. In the current study, in-silico drug repurposing techniques were employed to identify small natural molecules from the ZINC database as potential BACE-1 inhibitors. Molecular docking studies (both rigid and flexible) were conducted via high-throughput virtual screening, standard-precision and extra precision mode and protein ligand interactions were observed. Top compounds were undertaken for molecular mechanics with generalized Born and surface area solvation (MMGBSA) calculations and absorption distribution metabolism elimination properties analysis. ZINC000014945921, ZINC000150351431, and ZINC000069488328 were selected as leads and these compounds with the co-crystallized ligand were subjected to molecular dynamic simulations. The final findings of this study suggested that ZINC000150351431 and ZINC000069488328 can be considered as potential leads in the development of drugs for therapeutic use for AD.
Keywords: Natural, zinc data base, BACE-1, molecular mechanics with generalized born and surface area solvation (MMGBSA), high-throughput virtual screening (HTVS)